A framework for six-sigma implementation in rubber manufacturing industry – an innovation between DMAIC cycle and quality improvement tools - Zamri Darus,; Mohd Nizam Ab Rahman,; Rafique, Muhammad Zeeshan (Penerbit Universiti Kebangsaan Malaysia, 2019)
Quality improvement tools are commonly utilised by the industries to attain quality products and benefits like reduction in scrap cost and wastes. In order to achieve the proper implementation of quality tools, a theoretically developed framework inclusive of six-sigma DMAIC (Define, Measure, Analyse, Improve & Control) cycle is required. Also, the quality tools associated at each stage has thoroughly implemented on a case study which carries a real-time issue related to the quality products production. The issue has thoroughly resolved through the right application of quality tools like Failure Modes and effects analysis (FMEA) on the compression moulding technique utilised for the production of Rubber Valve Sleeve Liner (RVSL) under the umbrella of DMAIC cycle. The benefits achieved are 23.1% reduction in scrap rate, 63.8% reduction in Delivery on time (DOT) with savings gained almost RM26,880/month. The relationship between DMAIC cycle and quality tools for quality improvements under the platform of lean six sigma which is highly beneficial for academicians, practitioners and engineering managers working in this field with a limitation of implementation only in the rubber manufacturing industry. In future, the developed framework should be implemented in some other manufacturing industries.